Pelaksanaan Supervisi Pendidikan oleh Kepala Sekolah dalam Meningkatkan Profesionalisme Guru Bimbingan Konseling di SMP Negeri 8 Palopo - Sumardin Raupu; Dwi Risky Arifanti (Kelola: Journal of Islamic Education Management, 2019)
Educational supervision is an effort to guide school principals to teachers, and guidance counseling teachers in schools in order to improve the quality of teaching and learning in schools. The purpose of this study is to find out 1) The process of preparing the principal's supervision program in increasing the professional competence of the counseling guidance teacher, 2) The implementation of the educational supervision program by the principal in improving the professional competence of the counseling guidance teacher, and 3) The principal's follow-up in implementing the supervision of education for improve the professional competence of counseling guidance teachers. This research uses descriptive method with a qualitative approach. Data collection techniques are observation, interview and documentation. Research subjects were the principal, vice principal and counseling guidance teacher. The results of his research show that: 1) The supervision program of the headmaster of Palopo 8 Junior High School was prepared at the beginning of each semester of the school year by involving the deputy headmaster, counseling guidance teacher, and teacher in the field of study. The supervision program includes the activities of professional teacher guidance and guidance as well as training for teachers that are tailored to their fields. 2) The supervision of the head of SMP Negeri 8 Palopo follows the program that has been prepared, the technique used is through teacher meetings, classroom observations and personal conversations. Especially for classroom observation techniques, they have already used observation guidelines, but the quantity in the implementation has not been maximized. 3) The follow-up supervision of the headmaster of Palopo 8 Junior High School was observed through individual talks, giving advice, coaching, and guiding counseling guidance teachers with a focus on better implementation of activities, but the principal did not fully understand the counseling guidance program